The unlocked power of the agricultural sector: An economy-wide approach in South Africa - Damonse, Kyla (School of Economics, 2023)
With the use of an economy-wide perspective, this paper discusses the changing structure and role of the agricultural sector in South Africa. With South Africa facing a triple challenge of high rates of poverty, inequality, and unemployment, this paper argues that policy-makers should look to the agricultural sector to pragmatically achieve sustainable development. While structural change had been growth-enhancing in the early 1970s, many sectors of the economy have since failed to generate inclusive growth and employment opportunities for the vast majority of South Africans. Through multiplier analysis, this paper finds that there are considerable opportunities for development to be gained from investment in the agricultural sector. Indeed, especially in the context of a post-pandemic recovery, policy-makers must recognize the integral role of the sector in South Africa's development strategy.